2018
DOI: 10.1007/s12325-018-0777-y
|View full text |Cite
|
Sign up to set email alerts
|

A Charter to Improve Patient Care in Severe Asthma

Abstract: Severe asthma is a subtype of asthma that is difficult to treat and control. By conservative estimates, severe asthma affects approximately 5–10% of patients with asthma worldwide. Severe asthma impairs patients’ health-related quality of life, and patients are at risk of life-threatening asthma attacks. Severe asthma also accounts for the majority of health care expenditures associated with asthma. Guidelines recommend that patients with severe asthma be referred to a specialist respiratory team for correct d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 31 publications
0
80
0
Order By: Relevance
“…For each statement, participants were further asked whether available evidence was of sufficient quality and were also asked to score their level of conviction/support. Evidence was graded according to the Oxford levels of evidence document [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each statement, participants were further asked whether available evidence was of sufficient quality and were also asked to score their level of conviction/support. Evidence was graded according to the Oxford levels of evidence document [23].…”
Section: Methodsmentioning
confidence: 99%
“…These effects strongly impact quality of life. Fear of side-effects may induce a vicious circle related to poor adherence and poor control as well as medical nomadism [23]. In children, adverse behavioural effects of OCS bursts prescribed in asthma exacerbations have also been shown [145].…”
Section: Ocularmentioning
confidence: 99%
“…31 The authors suggested that the interventions should be done at the patient level, at the health Menzies-Gow et al offered six core principles: timely diagnosis, referral, support of patients by providing relevant information about asthma and personalized education, treatment not reliant on OCSs, and access to consistent quality care, to address the unmet need in treating severe asthma and to deliver improvements in asthma care. 32 These strategies, based on the latest understanding of the disease, should be used to benchmark current service provisions. The results of this study will help health-care professionals to identify those who are at a higher risk of dying and those who need more specialized attention.…”
Section: Discussionmentioning
confidence: 99%
“…Core management goals include timely and equitable access to severe asthma services, individualized management specific to the asthma phenotype and reduced AE associated with OCS. These goals are achievable if there is universal adoption of the principles by patients, healthcare professionals and policymakers, supported by appropriate resource allocation …”
Section: Barriers To and Solutions For Changementioning
confidence: 99%
“…In rheumatology, the advent of novel treatments, together with improved care through multidisciplinary teams, has revolutionalized treatment and substantially reduced OCS use . Recognition of the equivalent problem in respiratory medicine coupled to appropriate remedial strategies can therefore help to optimize OCS use …”
Section: Introductionmentioning
confidence: 99%